Gated Organonanoclays for Large Biomolecules: Controlled Release Triggered by Surfactant Stimulus - Elisa Poyatos-Racionero; Édgar Pérez-Esteve; Serena Medaglia; Elena Aznar; José M. Barat; Ramón Martínez-Máñez; Maria Dolores Marcos; Andrea Bernardos (Nanomaterials, 2022)
The low toxicity and high adsorption capacities of clay minerals make them attractive for controlled delivery applications. However, the number of controlled-release studies in the literature using clay minerals is still scarce. In this work, three different clays from the smectite group (Kunipia F, montmorillonite; Sumecton SA, saponite; and Sumecton SWN, hectorite) were successfully loaded with rhodamine B dye and functionalized with oleic acid as a gatekeeper to produce organonanoclays for active and controlled payload-release. Moreover, hematin and cyanocobalamin have also been encapsulated in hectorite gated clay. These organonanoclays were able to confine the entrapped cargos in an aqueous environment, and effectively release them in the presence of surfactants (as bile salts). A controlled delivery of 49 ± 6 μg hematin/mg solid and 32.7 ± 1.5 μg cyanocobalamin/mg solid was reached. The cargo release profiles of all of the organonanoclays were adjusted to three different release-kinetic models, demonstrating the Korsmeyer–Peppas model with release dependence on (i) the organic–inorganic hybrid system, and (ii) the nature of loaded molecules and their interaction with the support. Furthermore, in vitro cell viability assays were carried out with Caco-2 cells, demonstrating that the organonanoclays are well tolerated by cells at particle concentrations of ca. 50 μg/mL.